2021
DOI: 10.1590/1806-9061-2020-1314
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis Between Polymorphism of Gonadotrophin Releasing Hormone Genes and Growth Traits of Quail (Coturnix Coturnix)

Abstract: This study investigated SNP mutation sites of Gonadotrophin releasing hormone (GnRH) gene in China yellow quail, Beijing white quail and Korean quail through PCR amplification and DNA sequencing technologies. Moreover, polymorphism of GnRH gene and its association with growth traits of quail were analyzed, aiming to get molecular markers associated to growth traits of quail, which could provide references for breeding of new quail species. According to research results, a total of 14 SNP mutation sites of GnRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…A583T, C591T, and A592G sites were significantly associated with BW, SL, CW, BBL, and BL at 5 wk of age in SV, and individuals with the heterozygous mutation genotype of 3 sites had significantly higher BW, CW, BBL, and BL, and individuals with the wild genotype of 3 sites had higher SL ( P < 0.05). Similar to this study, a previous study in 3 strains of egg quail showed that 13 SNPs of the GnRH gene was significantly associated with growth traits ( Bai et al, 2021 ). This finding indicates that 8 SNPs of the GnRH gene may affect growth traits and could be used as novel molecular marker to in SV and FG strains in quail.…”
Section: Results and Disscusionsupporting
confidence: 89%
See 4 more Smart Citations
“…A583T, C591T, and A592G sites were significantly associated with BW, SL, CW, BBL, and BL at 5 wk of age in SV, and individuals with the heterozygous mutation genotype of 3 sites had significantly higher BW, CW, BBL, and BL, and individuals with the wild genotype of 3 sites had higher SL ( P < 0.05). Similar to this study, a previous study in 3 strains of egg quail showed that 13 SNPs of the GnRH gene was significantly associated with growth traits ( Bai et al, 2021 ). This finding indicates that 8 SNPs of the GnRH gene may affect growth traits and could be used as novel molecular marker to in SV and FG strains in quail.…”
Section: Results and Disscusionsupporting
confidence: 89%
“…The reaction conditions were as follows: initial denaturation at 94°C for 5 min, followed by 30 cycles of 94°C for 30 s, annealing for 59°C for 30 s, extension at 72°C for 1 min, and a final extension at 72°C for 10 min. The reaction system was stored under 4°C ( Bai et al, 2021 ). The PCR products of the GnRH gene were sent to Beijing Qingke biological Co., Ltd. for sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations